Ensaio clínico-terapêutico na leishmaniose visceral canina.: Imunoquimioterapia em animais assintomáticos - Marcia Almeida de Melo (1998)
The available drugs for treatment of human visceral leishmaniasis do not promote cure of the dogs Whereas new drugs are not available for use in dogs, it is necessary to test therapeutic trials using old drugs in association with other agents. The objective of this experiment was to test the therapeutic efficacy of the Glucantime® in association with an antigenic extract from Leishmania braziliensis in assymptomatic dogs expenmentally infected. Thirty-two laboratory reared mongrel dogs were infected with amstigotes of L. chagasi. Dunng 450 days, the follow up was done by specific antibody detection, cellular immune response, hematology, biochemical serology and detection of the parasite in boné marrow and skin. Alter the confirmation of the infection by antibody or parasite detection, the dogs were randomly allocated in four groups of eight animals each; Group A, received antigen (500 hg/day); Group B, received Glucantime® (100 mg/Kg/day); Group C, received the antigen plus Glucantime® and group D received no treatment. All dogs were killed and necropsied 450 days after inoculation. Bone marrow aspirate, spleen, popliteal lymph node, skin from ear were collected and stained with giemsa for microscopic examination. Tissue samples of skin from nose, ear, mesenteric and popliteal lymph nodes, kidney, spleen and liver , were processed by conventional method and stained with H & E. Spleen samples were inoculated into culture tubes containing NNN/LIT. Thirteen dogs were infeued. The antimonial was able to reduce the antibody levels and the parasitism but the dogs were not cured.